Validation of Finnish Diabetes Risk Score Indonesia Version in Yogyakarta - Pertiwi, Putri; Perwitasari, Dyah Aryani; Satibi, Satibi (Borneo Journal of Pharmacy, 2021)
Diabetes mellitus (DM) has developed as a major public health problem in the world. It is estimated that around 50% of diabetics have not been diagnosed in Indonesia, and only two-thirds of those diagnosed are undergoing treatment. This condition must be prevented. The purpose of this study is to determine the validity and reliability of the Indonesian version of FINDRISC as an instrument for predicting type 2 diabetes mellitus (T2DM). This study was an observational study with a cross-sectional design on 60 research subjects who are indigenous people of Yogyakarta who live in Yogyakarta, which can be proven by Identity Cards by the inclusion and exclusion criteria. Validity is tested by the validity of criteria by type while using the area under the receiver-operating curve (ROC-AUC), while reliability is tested by internal consistency using Cronbach's Alpha (α). The results showed that as many as 14 people, or 23.33% experienced uncontrolled fasting blood sugar and 15 people had a risk score of FINDRISC more than 10. Based on the ROC AUC analysis, the value of 0.935 (95% CI 0.865 1.00) with a cut-off point of 10 with the value of Sn = 85%, Sp = 95%, PPV = 85%, NPV = 95%, +LR = 5.66, and -LR = 0.15. Based on the reliability test, the Cronbach's value of 0.727 is obtained. The FINDRISC questionnaire is categorized as valid and reliable so that it can be a screening tool for understanding.